Problematika dan Tanggung Jawab Profesi Notaris kepada Masyarakat demi Tercapainya Kepastian Hukum - Anindita, Puspita; Priyono, Ery Agus (Universitas Muhammadiyah Ponorogo, 2025)
In order to realize the Republic of Indonesia as a State of Law based on Pancasila and the 1945 Constitution of the Republic of Indonesia in order to guarantee certainty, order and legal protection for those who need authentic written evidence which explains the circumstances, events or legal acts that require the Office of Notary, in 2004 the Republic of Indonesia Law Number 30 of 2004 concerning the Office of Notary was issued as amended by Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to the Republic of Indonesia Law Number 30 of 2004 concerning the Office of Notary. Based on the Provisions of Article 1 number 1 of the Republic of Indonesia Law Number: 30 of 2004 concerning the Position of Notary as amended by the Republic of Indonesia Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, the definition of Notary is as follows: Notary is a public official who is authorized to make authentic deeds and other authorities as referred to in this Law. Thus, because the Notarial Deed is an Authentic Deed, the Notarial Deed has perfect or complete evidentiary power, as stipulated in Article 165 HIR.